2016
DOI: 10.1007/s12149-016-1074-y
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a 68Ga-peptide tracer for PET GnRH1-imaging

Abstract: The peptide and the conjugates were synthesized with >95 % chemical purity. [(68)Ga]-DOTA-TRP complex was prepared in high radiochemical purity (>99 %, ITLC, HPLC) and specific activity of 1400-2100 MBq/nM at 95 °C using 40-60 μg of the peptide in 5-7 min followed by solid phase purification. The IC50 [nM] DOTA-TRP was comparable to the intact peptide, 0.11 ± 0.01 and 0.22 ± 0.05, respectively. The biodistribution of the tracer demonstrated kidney, stomach, and testes significant uptake, all in accordance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…GnRH peptide analogues labeled with positron-emitting radionuclides are of particular interest due to the high spatial resolution and sensitivity of PET [19]. Recently, Zoghi et al developed [ 68 Ga]-labeled DOTA-triptorelin as a possible PET radiotracer for GnRH receptor imaging [17]. The biodistribution of the tracer was determined in normal male rats and 4T1 tumor-bearing mice.…”
Section: Introductionmentioning
confidence: 99%
“…GnRH peptide analogues labeled with positron-emitting radionuclides are of particular interest due to the high spatial resolution and sensitivity of PET [19]. Recently, Zoghi et al developed [ 68 Ga]-labeled DOTA-triptorelin as a possible PET radiotracer for GnRH receptor imaging [17]. The biodistribution of the tracer was determined in normal male rats and 4T1 tumor-bearing mice.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies were done by three different procedures. The triptorelin‐hydrazide labeled with 177 Lu was evaluated in vitro using GnRH‐I expressing on the human prostatic carcinoma cell line LNCaP to determine receptor affinity and to assess internalization efficiency . Moreover, serum stability study was performed for 177 Lu‐DOTA‐TRPHYD.…”
Section: Introductionmentioning
confidence: 99%
“…)(2224). Zoghi et al from Iran reported on the synthesis and biodistribution studies of 68 Ga-DOTA-triptorelin ( 68 Ga-DOTA-TRP) as a PET radioligand targeted to the GnRH-R (25). The authors reported a robust synthesis scheme with the radiotracer biodistribution demonstrating significant uptake in kidney (excretion route), stomach, and testes.…”
Section: Oncologymentioning
confidence: 99%